Extradural Thoracic Spinal Cord Compression: Unusual Initial Presentation of Post-transplant Lymphoproliferative Disorder - Bakker, Nicholas A.; van Dijk, J. Marc C.; Slart, Riemer H.J.A.; Coppes, Maarten H.; van Imhoff, Gustaaf W.; Verschuuren, Eric A.M. (The Journal of heart and lung transplantation, 2008)
Post-transplant lymphoproliferative disorder (PTLD) is a serious complication after solid-organ transplantation. We report a lung transplant recipient presenting with lower limb weakness as a result of extradural cord compression from PTLD. Diagnosis was made by laminectomy of T-3 with partial removal of the epidural mass. Further treatment consisted of chemoradiotherapy. The patient recovered completely. To our knowledge, this is the first reported case of PTLD presenting with signs and symptoms of spinal cord compression. The differential diagnosis of spinal cord compression in a patient who has had a transplant should include primary presentation of PTLD.